The Lawyer-Client: A Managed Relationship? - Reed, John P. (Academy of Management Journal, 1969)
Through a management sequence, a random sample of 125 civil lawyers were shown to engineer and control the lawyer-client relationship rather than leave its development and outcome to chance. The sequence which produced a ?sifted clientele? and negatively created a legally indigent population was refusal, acceptance, maneuver, influence, decision, action, withdrawal, prolongation, and performance.